HISTORICAL LEGACY OF TOURISM IN KASHMIR VALLEY WITH SPECIAL REFERENCE TO DOGRA PERIOD - Shabir Ahmad Lone (PT. Radja Intercontinental Publishing, 2024)
This study delves into the historical backdrop of tourism in the Kashmir valley during the Dogra era. Despite Maharaja Gulab Singh establishing Dogra rule in 1846, little attention was given to promoting the tourism industry in Jammu and Kashmir until the establishment of the residency in 1885. It wasn't until the last two decades of the nineteenth century that Dogra rulers, in collaboration with British officials, initiated various measures to enhance tourism in Kashmir. This included improvements in communication, transportation, and infrastructure, along with the establishment of facilities to enhance air services for tourists.